Thionitrosyl‐ and Selenonitrosyliridium Complexes. Issue 20 (7th June 2013) - Scheibel, Markus G.; Klopsch, Isabel; Wolf, Hilke; Stollberg, Peter; Stalke, Dietmar; Schneider, Sven
Abstract: The activation of elemental sulfur and selenium with electrophilic iridium nitride [Ir(N)N(CHCHP t Bu2 )2 ] + allowed the synthesis of thionitrosyl‐ and selenonitrosyliridium complexes. The crystallographic and spectroscopic characterization of this rare series of chalcogenonitrosyl complexes [Ir(NE)N(CHCHP t Bu2 )2 ] + (E = none, O, S, Se) is discussed in the context of bonding models. The experimental results indicate strong Ir–N–E multiple‐bond character, in agreement with the previously proposed N–E donor–acceptor interaction as an appropriate description for the heavier chalcogens. Abstract : The nitridoiridium complex [Ir(N)N(CHCHP t Bu2 )2 ]PF6 is oxidized by elemental sulfur and selenium to the corresponding thionitrosyl and selenonitrosyl complexes to give access to a rare example for a full M(NE) (E = none, O, S, Se) series. Bonding is discussed on the basis of crystallographic and spectroscopic characterization.